2012
DOI: 10.5601/jelem.2013.18.1.07
|View full text |Cite
|
Sign up to set email alerts
|

Dietary chromium(III) propionate complex supplementation affects tissue mineral levels in rats fed high-fructose diet

Abstract: Chromium(III) plays an important role in carbohydrate and lipid metabolism, thus supplements containing this element are broadly advertised as efficient agents improving blood glucose levels or even reducing body mass. However, their hypoglycemic potential depends on the chemical form, bioavailability, dosage and the duration of treatment. Chromium(III) supplementation is generally considered safe although some data point to interaction of this ion with other elements. Thus, the aim of this study was to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Krejpcio et al [ 63 ] found that supplementation with Cr3 (5 mg· kg −1 of diet) did not affect Mg levels in Wistar rats. Król et al [ 64 ] showed that Cr3 supplementation disturb mineral homeostasis in the rats’ organs fed high-fructose diet. Cr3 increased Mg, Cu and Cr levels, although it did not influence tissular Ca, Fe and Zn contents, given for 4 weeks in doses 1 and 5 mg· kg −1 b.w.…”
Section: Discussionmentioning
confidence: 99%
“…Krejpcio et al [ 63 ] found that supplementation with Cr3 (5 mg· kg −1 of diet) did not affect Mg levels in Wistar rats. Król et al [ 64 ] showed that Cr3 supplementation disturb mineral homeostasis in the rats’ organs fed high-fructose diet. Cr3 increased Mg, Cu and Cr levels, although it did not influence tissular Ca, Fe and Zn contents, given for 4 weeks in doses 1 and 5 mg· kg −1 b.w.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased Zn levels in diabetes may have been caused by disordered intestinal Zn absorption mechanisms and its increased urinary excretion. On the other hand, some other studies [27, 51] did not report significant changes in Zn status in the course of diabetes.…”
Section: Discussionmentioning
confidence: 88%
“…The influence of diabetes on the Zn status has not been fully elucidated. In some animal trials [43] and clinical studies [5153], decreased Zn levels were noticed in tissues and serum/plasma, respectively. The decreased Zn levels in diabetes may have been caused by disordered intestinal Zn absorption mechanisms and its increased urinary excretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between an increased dietary Cr(III) intake and Fe stores was confirmed in several studies. For example, in our previous study, 8-week CrProp supplementation (1 mg Cr/kg b.m./day) decreased Fe kidney concentration [ 11 ]; in contrast, a 4-week administration of CrProp in the same dosages did not influence the examined parameters of iron status in rats fed a high-fructose diet [ 49 ]. In obese type 2 diabetic rats, supplementation of 1,000 μg Cr/kg b.m./day in the form of CrProp reduced kidney Fe level [ 12 ].…”
Section: Discussionmentioning
confidence: 99%